Integration of Nanobots Into Neural Circuits As a Future Therapy for Treating Neurodegenerative Disorders - Saniotis, Arthur; Henneberg, Maciej; Sawalma, Abdul-Rahman (Frontiers in Neuroscience, 2018)
Recent neuroscientific research demonstrates that the human brain is becoming altered by technological devices. Improvements in biotechnologies and computer based technologies are now increasing the likelihood for the development of brain augmentation devices in the next twenty years. We have developed the idea of a nanosymbiont cognitive enhancer (NCE) as a new kind of future neuroprosthetic which is based on nature’s endomyccorhiza. The nanosymbiont cognitive enhancers (NCEs) are nanobots which can be programmed to integrate with neurons. In theory, the NCE will be able to extend and amplify neuronal reaction to stimulatory and inhibitory signals via communicative coupling. This constant exchange of information will be vital for the NCE to learn the contextual pattern of its host and the neuronal environment. Consequently, such an integrative process would enable more neurons in networks participating in cognitive functions. The NCE may improve cognitive functions even if the exact knowledge of the location and connections of involved neuronal circuits is missing while their application will be minimally invasive compared to current methods of neurosurgery. Additionally, the NCE would seek to enhance neural processing speed and efficiency in both unhealthy and healthy subjects.